ADAPTASI MANTAN NARAPIDANA DI PEKANBARU - Tifany Deby Afisa; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The aim of this study is to find out how the effort and obstacles of ex-prisoner in doing adaptation. In choosing the sample of this research, the writer used purposive sampling technique which choosen bases on criteria. The quantity of informant in this research was 5 person. The theory used in this research is adaptation theory constructed by Robert. K. Merton. After analyzing the data researcher found that the exprisoner tried some effort in doing adaption there were change the way they clothing and their attitude, follow the habitualof their society and build interaction. The most effort who give significant effect to the ex-prisoner is build interaction and follow the habitual of society. Then the obstacles that faced by ex-prisoner is they attract their themselves from society because of unconfident to build the interaction. That is the efgortand obstacles faced by ex-prisoner in doing adaptation with their society.   Keywords: Adaptation, Ex-prisoner, Society